Effect of deficit irrigation on yield, quality, and costs of the production of native spearmint (2014)
Water-saving strategies aimed at improving water use efficiency need to be applied in agriculture today to ensure sustainable use of scarce water resources. This article presents results of a 2-year study done at Washington State University's Irrigated Agriculture Research and Extension Center (IAREC) to determine the effect of various water stress levels applied at various times during the growth period to the yield quantity, quality, and production costs of drip-irrigated native spearmint (Mentha spicata L.). The field experiment included four irrigation levels (40, 54, 80, and 100% of ETc) and four stress timings: T1(the irrigation levels were applied throughout the growing season), T2, T3, and T4 where the irrigation levels were applied 21, 14, and 7 days before harvest, respectively. Hay yields decreased with increasing water stress; mean annual hay yield ranged from 47.2 Mg/ha under the driest treatment (40% irrigation level at timing T1) to 61.2 Mg/ha under 100% irrigation level. Mean annual oil yields ranged between 108 and 147 kg/ha among treatments. Fully irrigated plots gave average oil yields of 127 kg/ha. Deficit irrigation thus has potential to give similar or even higher oil yields than those from fully irrigated plots. Water stress did not significantly affect oil quality. The oil concentration (kg of oil per kg of hay) increased with water stress; mean oil concentrations ranged from 0.22% under 100% irrigation level to 0.31% under the driest treatment.Water use efficiency (oil yield per unit volume of water consumed) also increased with increasing water stress, ranging from 0.009 kg/m3 under 100% irrigation level to 0.026 kg=m3 under the driest treatment. Costs of production savings were 2.9, 6.6, and 8.6% per hectare for the 80, 54, and 40% of ETc, respectively, when compared to the full irrigation scenario. Results show that up to 60% irrigation deficit in native spearmint, no matter its timing, can save water, improve water use efficiency, and reduce costs of production while maintaining oil yields and quality similar to those from fully irrigated plants. © 2014 American Society of Civil Engineers.